Curriculum Decision Making in Australian Early Childhood Settings Do Early Childhood Teachers Really Plan from a Theoretical Basis? - Clyde, Margaret ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
A preliminary study assessed the efficacy of pre-service and in-service early childhood education programs centered on a policy of combining philosophy, theory, and program practice. Questions were designed to: (1) provide data to be used to determine whether early childhood teachers used an understanding of curriculum philosophy and theory as a basis for program planning; (2) generate information related to the topic of program planning; and (3) permit the development of an instrument that could be used throughout the early childhood field as a basis for gathering data for the purpose of enhancing university in-service and pre-service curriculum planning courses. Results of the pilot study supported the notion that some early childhood educators use an understanding of curriculum philosophy and theory as a basis for program planning. Whether this knowledge is related to participants' pre-service or in-service education, or a combination of the two, remains unclear. (RH)
ERIC Note: Paper presented at the Annual International Conference on Early Education and Development (21st, Hong Kong, July 31-August 4, 1989).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Development; Decision Making; Early Childhood Education; Educational Philosophy; Educational Research; Educational Theories; Foreign Countries; Inservice Teacher Education; Teacher Behavior; Teacher Qualifications; Theory Practice Relationship; Australia; Reports, Research; Speeches/Meeting Papers